Laparoscopy‐assisted immediate vaginal reconstruction with a vertical pedicled deep inferior epigastric perforator flap for primary melanoma of the vagina - Dupré, Pierre‐François; Legoupil, Delphine; Vigouroux, Camille; Conan‐Charlet, Virginie; Kergastel, Isabelle; Merviel, Philippe; Kerfant, Nathalie (Clinical case reports, 2021)
The vagina is a rare site for primary melanoma. Here, we report on a case of laparoscopy‐assisted immediate vaginal reconstruction with vertical pedicled deep inferior epigastric perforator flap. The vagina is a rare site for primary melanoma. Here, we report on a case of laparoscopy‐assisted immediate vaginal reconstruction with vertical pedicled deep inferior epigastric perforator flap.